Plasma concentrations of persistent organic pollutants and pancreatic cancer risk. (14th July 2021) - Porta, Miquel; Gasull, Magda; Pumarega, José; Kiviranta, Hannu; Rantakokko, Panu; Raaschou-Nielsen, Ole; Bergdahl, Ingvar A; Sandanger, Torkjel Manning; Agudo, Antoni; Rylander, Charlotta; Nøst, Therese Haugdahl; Donat-Vargas, Carolina; et al.
Abstract: Background: Findings and limitations of previous studies on persistent organic pollutants (POPs) and pancreatic cancer risk support conducting further research in prospective cohorts. Methods: We conducted a prospective case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Participants were 513 pancreatic cancer cases and 1020 matched controls. Concentrations of 22 POPs were measured in plasma collected at baseline. Results: Some associations were observed at higher concentrations of p, p' -DDT, trans-nonachlor, β-hexachlorocyclohexane and the sum of six organochlorine pesticides and of 16 POPs. The odds ratio (OR) for the upper quartile of trans-nonachlor was 1.55 (95% confidence interval 1.06-2.26; P for trend = 0.025). Associations were stronger in the groups predefined as most valid (participants having fasted >6 h, with microscopic diagnostic confirmation, normal weight, and never smokers), and as most relevant (follow-up ≥10 years). Among participants having fasted >6 h, the ORs were relevant for 10 of 11 exposures. Higher ORs were also observed among cases with microscopic confirmation than in cases with a clinical diagnosis, and among normal-weight participants than in the rest of participants. Among participants with a follow-up ≥10 years, estimates were higher than in participants with a shorter follow-up (for trans-nonachlor: OR = 2.14, 1.01 to 4.53, P for trend = 0.035). Overall, trans-nonachlor, three PCBs and the two sums of POPs were the exposures most clearly associated with pancreatic cancer risk. Conclusions: Individually or in combination, most of the 22 POPs analysed did not or only moderately increased the risk of pancreatic cancer.